Xkr8 Modulates Bipolar Cell Number in the Mouse Retina - Kautzman, Amanda G.; Keeley, Patrick W.; Ackley, Caroline R.; Leong, Stephanie; Whitney, Irene E.; Reese, Benjamin E. (Frontiers in Neuroscience, 2018)
The present study interrogated a quantitative trait locus (QTL) on Chr 4 associated with the population sizes of two types of bipolar cell in the mouse retina. This locus was identified by quantifying the number of rod bipolar cells and Type 2 cone bipolar cells across a panel of recombinant inbred (RI) strains of mice derived from two inbred laboratory strains, C57BL/6J (B6/J) and A/J, and mapping a proportion of that variation in cell number, for each cell type, to this shared locus. There, we identified the candidate gene X Kell blood group precursor related family member 8 homolog (Xkr8). While Xkr8 has no documented role in the retina, we localize robust expression in the mature retina via in situ hybridization, confirm its developmental presence via immunolabeling, and show that it is differentially regulated during the postnatal period between the B6/J and A/J strains using qPCR. Microarray analysis, derived from whole eye mRNA from the entire RI strain set, demonstrates significant negative correlation of Xkr8 expression with the number of each of these two types of bipolar cells, and the variation in Xkr8 expression across the strains maps a cis-eQTL, implicating a regulatory variant discriminating the parental genomes. Xkr8 plasmid electroporation during development yielded a reduction in the number of bipolar cells in the retina, while sequence analysis of Xkr8 in the two parental strain genomes identified a structural variant in the 3' UTR that may disrupt mRNA stability, and two SNPs in the promoter that create transcription factor binding sites. We propose that Xkr8, via its participation in mediating cell death, plays a role in the specification of bipolar cell number in the retina.